A novel cathodic composite in lithium ion battery based on LiNi0.7Co0.3O2, Li2MnO3, and LiCoO2 combination: synthesis and characterisation. (10th November 2020) - Pham, Thu Thi; Mollaamin, Fatemeh; Monajjemi, Majid; Alihosseini, Afshar; Moghaddam, Amin Hedayati; Dang, Chien Mau
Various composites including (1-x-y) LiNi0.7 Co0.3 O2, xLi2 MnO3 and yLiCoO2 systems were synthesised using the sol-gel method. Stoichiometric weights of the LiNO3, Mn(Ac)2 ·4H2 O, Co(Ac)2 ·4H2 O, Ni(NO3 )2 ·6H2 O for preparing of 28 samples have been used. We found that the sample "Li1.167 Ni0.117 Co0.699 Al0.017 Mn0.167 O2 " with Al doped is the best composition for cathode material in LIBTs. Obviously, the weight of cobalt used in this sample is lower compared to LiCoO2 which is an advantage in view point of cost and toxicity. Charge-discharge characteristics of the mentioned cathode materials were investigated by performing cycle tests in the range of 2.4-4.6 V. Our results confirmed that this kind of system can help removing the mentioned disadvantage of cobalt with high efficiency.